Head up its posterior lobe, a reply to Agnolín and Chimento (2025) - Vlachos, Evangelos (2025)
Recently, Agnolín and Chimento (2025) erected a new species of land tortoise, called Chelonoidis pucara Agnolín & Chimento, 2025, from the Pleistocene of Buenos Aires Province, Argentina, based on the holotype MLS 227, identified as “the anterior half of the plastron of an adult male individual”. Based on this identification, the authors recognize peculiar and unique characters, including the absence of a gular pocket and epiplastral lip, the presence of horn-like projections, and the presence of a large entoplastron with a midline suture, allowing the identification of a new species of Chelonoidis. Careful examination of the figures and drawings of Agnolín and Chimento (2025, figs. 2A-C, fig. 3A) reveals a misidentification of the specimen: what is identified as the anterior half of the plastron is actually the posterior half — the images need to be rotated 180 degrees. If done, then the morphology becomes clear. Seen properly, the characters observed in the holotype of Chelonoidis pucara are not enough to distinguish a new species of tortoise or Chelonoidis, therefore Chelonoidis pucara is considered invalid and more specifically, a nomen dubium.